2010
DOI: 10.1590/s1516-05722010000100014
|View full text |Cite
|
Sign up to set email alerts
|

Siparuna guianensis Aublet (negramina): uma revisão

Abstract: RESUMO:As pesquisas realizadas a partir de recursos genéticos de espécies medicinais nativas somente serão aplicadas se o material genético estiver seguro quanto à sobrevivência e disponibilidade. O objetivo deste artigo foi realizar uma revisão bibliográfica adotando como critério a escolha de artigos publicados em conceituadas revistas nacionais e internacionais, que permitissem melhor entendimento dos aspectos etnobotânicos, ecológicos e químicos de importante planta medicinal e aromática: Siparuna guianens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 26 publications
(15 reference statements)
2
21
0
3
Order By: Relevance
“…Several species of this genus are used in traditional medicine to handling stomach disorders and skin diseases (Leitão et al, 1999). Literature reports the use of S. guianensis leaves in popular medicine to cure various diseases, including, sinusitis, fever, rheumatism, migraine, body aches and as anti-infl ammatory (Valentini et al, 2010;Rodrigues, 2006). In state of Rondônia, Brazil (an oriental Amazonian state), there are some reports of using leaves tea in treatment of malaria and against rheumatic pains.…”
Section: Introductionmentioning
confidence: 99%
“…Several species of this genus are used in traditional medicine to handling stomach disorders and skin diseases (Leitão et al, 1999). Literature reports the use of S. guianensis leaves in popular medicine to cure various diseases, including, sinusitis, fever, rheumatism, migraine, body aches and as anti-infl ammatory (Valentini et al, 2010;Rodrigues, 2006). In state of Rondônia, Brazil (an oriental Amazonian state), there are some reports of using leaves tea in treatment of malaria and against rheumatic pains.…”
Section: Introductionmentioning
confidence: 99%
“…The use of this plant was identified in Central and South America in the traditional medicine through remedy baths, and juice and tea were also prepared using its leaves to combat fevers, rheumatic diseases, cramps, and high blood pressures. It was also used as an antibiotic, aromatic, diuretic, and stimulant (Approbato and Godoy, 2006;Furtado, 2006;Souza and Felfile, 2006;Valentini et al, 2010a;Pereira and Silva, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Other ethnobotanical studies have revealed the traditional use of this plant for combating sinuses, headaches, migraines, and body aches, acting as an analgesic and anti-inflammatory agent (Valentini et al, 2010a;Andrade et al, 2015). It has also been reported to be used for fluctuation of consciousness between hypoactive and hyperactive states, neck pains, muscle strains, fears, vomiting, and seizures (Pagania et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Siparuna guianensis Aublet, espécie medicinal e aromática, conhecida em Mato Grosso como negramina, é um arbusto encontrado no Cerrado que tem várias indicações terapêuticas, especialmente para gripe, dor de cabeça, reumatismo e "malina" (VALENTINI et al, 2010), e tal como outras espécies dessa fitofisionomia sofre a ação do extrativismo, do fogo e da substituição por pastos e monoculturas e, no caso do município de Cuiabá, pela ocupação antrópica que tem adentrado as áreas dos Parque e Bosques.…”
Section: Introductionunclassified
“…Siparuna guianensis Aublet, espécie medicinal e aromática, conhecida em Mato Grosso como negramina, é um arbusto encontrado no Cerrado que tem várias indicações terapêuticas, especialmente para gripe, dor de cabeça, reumatismo e "malina" (VALENTINI et al, 2010), e tal como outras espécies dessa fitofisionomia sofre a ação do extrativismo, do fogo e da substituição por pastos e monoculturas e, no caso do município de Cuiabá, pela ocupação antrópica que tem adentrado as áreas dos Parque e Bosques. Ribeiro et al (1981), trabalhando com espécies nativas do Cerrado, salientaram que um dos passos iniciais para o conhecimento e utilização dessas espécies é o estudo de sua biologia e, em particular, o de sua fenologia, e Vieira et al (2003) ressalvaram a importância de uma rápida ação das instituições no sentido de resgatar, conservar "ex situ", estudar e promover a domesticação dessas espécies.…”
Section: Introductionunclassified